EVALUASI PENGGUNAAN SATU NILAI TERTENTU (SINGLE AMOUNT) PADA KESIMPULAN NILAI DALAM LAPORAN PENILAIAN MENURUT SE-54/PJ/2016 - Sopian, Hendri (Politeknik Keuangan Negara STAN, 2024)
In the provisions of General Standard Standar Penilaian Indonesia (SPI) 105 concerning valuation reporting, it is stated that the final value conclusion can be expressed as a single value in rupiah currency. The value conclusion provisions in International Valuation Standards (IVS) are not even explicitly locked in, whether in single or range form. In the Circular Letter (SE) of the Director General of Taxes Number SE-54/PJ/2016, it is stipulated that the value conclusion is expressed in one particular value (a single amount) in rupiah currency units. The research uses normative-empirical research methods with a judicial case study approach and qualitative research with a descriptive analysis approach. The research results show that the value indications produced by the Appraiser can differ from one Appraiser to another. Even with the same market or comparative data, due to adjustment factors and different professional considerations for each Appraiser, it will certainly produce different value indications. Then the phrase